AI-Assisted TAVR Planning: Accuracy and Clinical Implications in Annulus Measurements - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Explore how AI enhances TAVR planning accuracy with precise annulus measurements, improving valve sizing and reducing procedural risks in severe aortic stenosis patients.
Keywords: TAVR; Artificial Intelligence; Cardiac Imaging; Valve Replacement; Digital Health